2020
DOI: 10.1080/19420862.2019.1698128
|View full text |Cite
|
Sign up to set email alerts
|

The impact of proline isomerization on antigen binding and the analytical profile of a trispecific anti-HIV antibody

Abstract: Proline cis-trans conformational isomerization is a mechanism that affects different types of protein functions and behaviors. Using analytical characterization, structural analysis, and molecular dynamics simulations, we studied the causes of an aberrant two-peak size-exclusion chromatography profile observed for a trispecific anti-HIV antibody. We found that proline isomerization in the tyrosine-proline-proline (YPP) motif in the heavy chain complementarity-determining region (CDR)3 domain of one of the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…During the submission stage of this manuscript Masiero et al, reported their findings of proline isomerization within a trispecific mAb that included 10E8v4 Fab (the same 10E8/iMab construct examined here) and the effect was localized to the same YPP motif we have implicated here 40 . Based on molecular dynamics simulations the authors concluded that the two observed conformers reflect the Y trans P trans P and Y trans P cis P forms.…”
Section: Biological Implications Of Cis/trans Proline Isomerization mentioning
confidence: 59%
“…During the submission stage of this manuscript Masiero et al, reported their findings of proline isomerization within a trispecific mAb that included 10E8v4 Fab (the same 10E8/iMab construct examined here) and the effect was localized to the same YPP motif we have implicated here 40 . Based on molecular dynamics simulations the authors concluded that the two observed conformers reflect the Y trans P trans P and Y trans P cis P forms.…”
Section: Biological Implications Of Cis/trans Proline Isomerization mentioning
confidence: 59%
“…34 Most recently, Masiero et al determined that the pH dependence of two interconverting peaks observed in the size exclusion chromatography profile of a trispecific anti-HIV antibody resulted from a conformational equilibria involving proline isomerization in the HC-CDR3 and a neighboring histidine in the light chain. 46 While each of these reports describes one or more of the phenomena we observed during our investigation of mAb-1, none of them account for the totality of our observations.…”
Section: Discussionmentioning
confidence: 82%
“…Amide-bond rotation is known as an intrinsically slow process, which contributes to the rate-limiting steps in the protein folding [ 91 ] and molecular timing phenomena [ 92 ]. In peptidyl-prolyl bonds, the transition between the rotational states cis -amide and trans -amide usually occurs in the mHz scale, with the barriers of rotation around 80–90 kJ mol −1 (in water).…”
Section: Resultsmentioning
confidence: 99%